2015
DOI: 10.1002/cpt.211
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring of monoclonal antibodies in inflammatory and malignant disease: Translating TNF‐α experience to oncology

Abstract: Lack of response to monoclonal antibodies (mAbs) has been associated with inadequate mAb serum concentrations. Therapeutic drug monitoring (TDM) of mAbs has the potential to guide to more effective dosing in individual patients. This review discusses the mechanisms responsible for interpatient variability of mAb pharmacokinetics, summarizes exposure-response data of mAbs used in inflammatory and malignant disease, presents current evidence of mAb-TDM in inflammatory disease, and provides hurdles and required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 76 publications
0
78
0
3
Order By: Relevance
“…In the current review describing the need for therapeutic drug monitoring (TDM) in inflammatory and malignant disease treated with mAbs, 4 the authors cite significant between-subject variability (BSV) reported for various mAbs (e.g., BSV for infliximab clearance of 34%; BSV for trastuzumab clearance 43%).…”
Section: Dr Mouldmentioning
confidence: 97%
See 3 more Smart Citations
“…In the current review describing the need for therapeutic drug monitoring (TDM) in inflammatory and malignant disease treated with mAbs, 4 the authors cite significant between-subject variability (BSV) reported for various mAbs (e.g., BSV for infliximab clearance of 34%; BSV for trastuzumab clearance 43%).…”
Section: Dr Mouldmentioning
confidence: 97%
“…Similar benefits from TDM have been shown in other inflammatory diseases 7 with other anti-TNF agents (see ref. 4 for more information). Although TDM is not specifically recommended in package inserts for mAbs used to treat inflammatory diseases, it has nonetheless become an important component of therapy.…”
Section: Dr Mouldmentioning
confidence: 97%
See 2 more Smart Citations
“…If the patient has a low MAb concentration in the presence of ADAs, the physician may switch the patient to another MAb in the same class, or it may be necessary to switch the patient to therapy with a different target (15). For other MAbs outside the IBD setting, comprehensive studies showing the links among MAb concentrations, loss of response, and outcomes are not available and the recommendations for patient management based on serum monitoring of MAb concentrations is less clear, although it seems that the TNF-α inhibitor experience can be translated to other areas (21, 22). …”
Section: Why Measure Therapeutic Mabs In the Clinical Laboratorymentioning
confidence: 99%